Sistem Informasi Penyewaan Perlengkapan Pelaminan Pada Paris Pesta Di Kota Padang Berbasis Web - Sari, Mike Febri Mayang; Suherman, Yanni; Azandra, Erien Nada; Samir, Haddad; Harto, Budi; Steffanie, Reggina Amelia (Kesatria : Jurnal Penerapan Sistem Informasi (Komputer dan Manajemen), 2024)
This research was conducted at Paris Pelaminan Party, especially in the administration section, which aims to assist administration in simplifying the process for customers in renting wedding equipment, making it easier for administration to process wedding equipment rental data and presenting reports to management. This research uses field research methods, library research, while the development method in this research is made using the Prototype method. The process and stages of prototyping and system development, it is hoped that after identifying user needs, the software created can be accepted by users. The information system designed is web-based, using the PHP programming language with Codeigniter 4 and MySQL database. This research produces an information system for wedding rental equipment so that this data management system can help the administration process rental data, make it easier for customers to rent, and present reports to management that are processed systematically, quickly, accurately, up to date, and practically to avoid errors in data management, so that problems at the Paris Bride Party can be resolved.